Numerical study of soliton generation in microresonators - Mezban, Hawraa A.; Sultan, H. A.; Mghames, Aqeel L. (Iraqi Journal of Science, 2025)
Soliton generation in microresonator is studied numerically using the Lugiato-Lefever equation (LLE). Optically induced effects, duration, and shape are studied via the adaptive split-step Fourier method (SSFM). It investigates how the microresonator affects the evolution of the optical field in cases of nonlinearity, dispersion, slow time, and fast time. A study is done on the optical frequency comb produced and the frequency domain dynamics of the microresonator. The generated soliton wave was a dispersive soliton. The study shows that the soliton generation and its properties depend strongly on the parameters included in this study.